Phenotypic and transcriptomic responses of diverse rice accessions to transient heat stress during early grain development - Nalini Chandran, Anil Kumar; Paul, Puneet; Dhatt, Balpreet K.; Sandhu, Jaspreet; Irvin, Larissa; Oguro, Shohei; Shi, Yu; Zhang, Chi; Walia, Harkamal (Frontiers in Plant Science, 2024)
Heat stress (HS) occurring during the grain-filling period has a detrimental effect on grain yield and quality in rice (Oryza sativa). The development of heat-resilient cultivars could partly solve this issue if tolerant alleles can be identified and incorporated into the germplasm. In this study, we posit that some of the phenotypic variation for heat resilience during grain development could be due to variations in gene expression among accessions. To test this, we characterized the HS response of 10 diverse rice accessions from three major sub-populations using physiological and transcriptomic analyses. At a single grain level, grain width and grain thickness emerged as the most heat-sensitive traits. During a transient HS, IND-3 was categorized as highly sensitive, while five accessions exhibited moderate heat sensitivity, and four accessions were tolerant. Only a core set of 29.4% of the differentially expressed genes was common to the three rice subpopulations. Heat-tolerant accession, TEJ-5 uniquely triggered an unfolded protein response (UPR) under HS, as evident from the induction of OsbZIP50 and downstream UPR genes. OsbZIP58, a gene that positively regulates grain-filling, was more highly induced by HS in IND-2 despite its moderate heat-sensitivity. Collectively, our analysis suggests that both unique gene expression responses and variation in the level of responses for a given pathway distinguish diverse accessions. Only some of these responses associate with single grain phenotypes in a manner consistent with the known roles of these genes and pathways. Keywords: Oryza sativa, heat stress, transcriptome, grain development, unfolded protein response Introduction Climate change-driven rise in global surface mean temperature and frequent heat waves are predicted to compromise crop production and food security. The mean global surface temperature is projected to increase by up to 4.8 °C by 2100 (Song et al., 2022). In addition to